Processed ship-based Navigation Data from the Amundsen Sea, Antarctica acquired during the Nathaniel B. Palmer expedition NBP1005 (2010) (IEDA: Marine-Geo Digital Library, 2011)
This data set was acquired with a ship-based Navigation system during Nathaniel B. Palmer expedition NBP1005 conducted in 2010 (Chief Scientist: Dr. Patricia Yager). These data files are of SHP format and include Primary Navigation data and were processed after data collection. Data were acquired as part of the project(s): ASPIRE (Amundsen Sea Polynya International Research Expedition), and funding was provided by NSF grant(s): ANT08-39069.